HIGH-PERFORMANCE STORAGE: THE FOUNDATION OF MODERN CLOUD COMPUTING - Kasthuri Theja Peduru, (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
The evolution and future trajectory of high-performance storage solutions are reshaping modern computing environments. From performance metrics and scalability challenges to data-intensive applications and security considerations, storage technology continues to transform traditional architectures. Emerging technologies like NVMe, edge computing, and AI-driven storage management address the growing demands of cloud computing, real-time processing, and distributed systems. These advancements significantly impact operational efficiency, cost optimization, and regulatory compliance across various industry sectors, while enabling organizations to meet increasingly complex data management requirements.